Effects of Social Networks on Job Attainment and Match Quality: Evidence from the China Labor-Force Dynamics Survey - Peng Nie; Weibo Yan (Institute of Labor Economics (IZA), 2021)
Using nationally representative data from the 2012 and 2014 China Labor-force Dynamics Survey, this paper investigates the effects of network types (kinship/non-kinship) and network resources (information/influence) on job attainment and match quality in China. We find a wage premium obtained through both kinship and non- kinship networks but shorter job duration only in jobs obtained through non-kinship networks. In regards to the different types of networks, resources embedded in the networks are not important. This conundrum can be reconciled if we take the structure of the network and the type of work unit into account. Kinship networks are more pervasive in the public sector, with better earnings and stable job positions. Non-kinship networks bring about a wage premium but lead to job dissatisfaction, especially in regards to promotion opportunities. This paper highlights the structure of the job market when studying networks and sheds new light on the types of networks that really matter in job attainment and those that result in the possible loss of match quality.
Keywords: J30; J31; J64; 330; network types; network resources; job attainment; match quality